A new leafhopper genus and four new species from the Grassland Biome of South Africa (Hemiptera, Cicadellidae) - Stiller, M. (Zootaxa, 2011)
A new endemic deltocephaline leafhopper, Tetramelasma gen.n. is described from the Grassland Biome of South Africa, comprising four new species: T. litopyx sp. n., T. nodosatha sp. n., T. scolosatha sp. n. and T. tanyphysis sp. n. Two paired dark markings on the vertex of the head are striking features of this genus and it is found in association with a number of grass species usually at high altitudes in the Grassland Biome. Species of this genus are characterized in the male by a short, truncated plate with a dorsal sclerotized process, the aedeagus with a long, slender shaft that is fused with the connective. Tribal placement in Deltocephalini is based on the fusion between the aedeagus and connective. The style has the posterior apophysis short and hollow or elongate and somewhat serrated. Females are characterized by the sternite 7 that is deeply invaginated along the posterior margin or only with a shallow notch, semicircular and sclerotized laterally.